Liquid biopsy can detect BRCA2 gene variants in female dogs with mammary neoplasia - de Oliveira, Jéssica Rodrigues [UNESP]; Colombo, Jucimara; Gonçalves, Francine Moraes; de Carvalho, Lucas Amoroso Lopes [UNESP]; Costa, Douglas Santos; Henrique, Tiago; Novais, Adriana Alonso; Moschetta-Pinheiro, Marina Gobbe; Chuffa, Luiz Gustavo de Almeida [UNESP]; Coutinho, Luiz Lehmann; Santana, Áureo Evangelista [UNESP]; Zuccari, Debora Aparecida Pires de Campos [UNESP] (Wiley, 2022)
Mammary tumours (MT) are one of the most prevalent malignancies in female dogs and women. Currently, molecular analyzes have shown that each tumour type presents its own genetic signature. In this context, liquid biopsy allows a comprehensive genetic characterisation of the tumour, enabling early diagnosis and personalised treatment of patients. In women, deleterious mutations inherited in BRCA2 gene are associated with an increased risk of breast cancer, resistance to therapies and worse prognosis. In female dogs, there are many divergent data on the involvement of BRCA2 gene with mammary carcinogenesis and what its pathogenic potential is. Therefore, the objective was to identify BRCA2 gene variants in 20 plasma DNA samples, from 10 newly diagnosed dogs with mammary cancer (RD), five control (CTR) and five mastectomized patients. Eleven single nucleotide polymorphisms (SNPs) were detected, most of them in the exon 11 and two indels (deletion/insertion) in the BRCA2 gene. However, there was no statistically significant difference in the SNPs/indels detected between the groups. In addition, only one SNP (p.T1425P) and one deletion (p.L2307del) were considered deleterious using in silico computational models. Interestingly, most common variants were present in the plasma of all groups, except for the Ile2614Thr, Ile2614Val, Thr1425Pro and p.L2307del variants. Thus, we observed that SNPs are common in the BRCA2 gene of female dogs with MT, with a similar condition identified in women with breast cancer. Liquid biopsy approach in dogs with MT is useful for genetic and therapeutic proposals.
Keywords: BRCA2 gene; breast cancer; dogs; genetic variants; personalised medicine